2021
DOI: 10.3390/nu13103431
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Diversity and Undernutrition in Children Aged 6–23 Months in Sub-Saharan Africa

Abstract: Dietary diversity plays a major role in the health status of children. However, evidence on its crucial role on children’s health status remains inconclusive in sub-Saharan Africa (SSA). In this study, we examined the association between dietary diversity and undernutrition among children aged 6–23 months in SSA. We pooled data from the most recent Demographic and Health Surveys of 32 countries in SSA from 2010 to 2020. A sample of 48,968 mother-child pairs of children within the ages of 6–23 months and mother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
36
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 41 publications
11
36
1
1
Order By: Relevance
“…We included a total of 18 covariates in our study. We selected the variables based on their availability in the DHS dataset and their association with childhood undernutrition from previous studies [ 20 , 28 , 30 ]. The variables were categorised into individual level factors, household factors, and contextual factors.…”
Section: Methodsmentioning
confidence: 99%
“…We included a total of 18 covariates in our study. We selected the variables based on their availability in the DHS dataset and their association with childhood undernutrition from previous studies [ 20 , 28 , 30 ]. The variables were categorised into individual level factors, household factors, and contextual factors.…”
Section: Methodsmentioning
confidence: 99%
“…Studies showed that children with an adequate minimum dietary diversity less likely to be stunted and underweight [ 3 , 12 ]. However, a lack of nutritional variety increases the morbidity and mortality of children [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moraeus et al [11], [31], [32], [10], [30], [31], [8], [28], [29], [8], [27], [28] which provides an explanation that eating culture in the family affects minimal dietary diversity so that it reduces the Z score and body mass index of children [8], [27], [28], [29].…”
Section: This Opinion Has Similarities With Research Conducted By De ...mentioning
confidence: 99%
“…Early provision of complementary food is at risk for nutritional inadequate where essential protein metabolism is slower than the body's carbohydrate metabolism [49], [23], [28], [50]. This condition has an impact on the delay in the formation of muscle and bone mass and tends to increase fat mass in the body.…”
Section: This Opinion Has Similarities With Research Conducted By De ...mentioning
confidence: 99%